Juan Benet and the “Outside”: A Blanchotian Reading - Navajas Espinal, Laura (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
The aim of this article is to analyze Juan Benet’s work, in particular his novel Un viaje de invierno, under the perspective of the Blanchotian literary space and the Foucaultian thinking of the outside also developed from Maurice Blanchot’s theoretical proposals. This will be supported by some of Benet’s essays: “El ángel del Señor abandona aTobías”; “Un extempore”; “Op. Posth.”; and “Un ensayo: La deuda de la novela hacia el poema religioso de la antigüedad”. My main interest is to dissociate hermeneutics of Benet’s work from historical, political, and social aprioris which condition the perspectives of analysis and to propose a new exegetical approach centered on the reflection about the literary fact itself, about its close connection with death, and about the impossibility to experience the event itself unless it is as an absence, as a trace or footprint, all in all, about the uselessness of any memory or testimony.